A user interactive decision-making approach for the improvement of energy efficiency in buildings: Α realistic case study - Diakaki, Christina (International Conference on Business and Economics - Hellenic Open University, 2025)
Improving energy efficiency in buildings is a major priority and challenge worldwide, as the available measures vary in nature, and the resulting decision problem becomes complex, due to the numerous decision variables involved, which reflect the alternative measures available, and the multiple, usually competitive objectives, in terms of cost, energy consumption, environmental concerns, etc., of the respective decision-maker, who is usually the user, occupant, and/or owner of the building. Another challenge arises from the need to satisfy the preferences of the involved decision-maker, which can be hardly prescribed, and should be elicited in a rather indirect way. To address the above challenges, a mixed-integer nonlinear mathematical programming model has been integrated with the UTASTAR value elicitation method, under an interactive decision making framework. To examine the feasibility and efficiency of the integrated decision making approach, an existing building is examined under realistic operating conditions. The study confirms the feasibility and efficiency of the approach, demonstrates its functionality, exploits its qualities, and highlights its strengths, weaknesses and limitations. JEL Classifications: C61, C63, C69, Q49 Keywords: Buildings’ energy efficiency improvement, Multi-objective optimization, Multi-criteria decision aid, Value system, Preference elicitation